2004
DOI: 10.1111/j.1460-9568.2004.03600.x
|View full text |Cite
|
Sign up to set email alerts
|

SNAP‐25 in hippocampal CA1 region is involved in memory consolidation

Abstract: As a synaptosomal protein, SNAP-25 plays a role in a number of neuronal functions including axonal growth, dendrite formation, fusion of synaptic vesicles with membrane and the expression of long-term potentiation (LTP) in the hippocampus. Using a learning ⁄ memory behavior screening, we identified SNAP-25 as one of the differentially expressed genes in the hippocampus upon behavioral training. The inhibition of SNAP-25 with intracerebroventricular antisense oligonucleotide caused a deficit in long-but not sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 53 publications
2
38
2
Order By: Relevance
“…In Alzheimer's disease and other dementia-related disorders, there is a significant decrease of synaptophysin expression in the presynaptic vesicles due, in part, to synapse loss. As hypothesized, loss of immunoactivity for the presynaptic vesicle marker proteins SNAP-25 may contribute to the progression of memory decline in patients with Alzheimer's disease [36,37].…”
Section: Discussionmentioning
confidence: 98%
“…In Alzheimer's disease and other dementia-related disorders, there is a significant decrease of synaptophysin expression in the presynaptic vesicles due, in part, to synapse loss. As hypothesized, loss of immunoactivity for the presynaptic vesicle marker proteins SNAP-25 may contribute to the progression of memory decline in patients with Alzheimer's disease [36,37].…”
Section: Discussionmentioning
confidence: 98%
“…Total RNA (10 g) from P19 cells during neural differentiation was analyzed by Northern blot as described previously (32). Reverse transcription was performed with 5 g of total RNA using SuperScript II reverse transcriptase (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this protein participates in the consolidation of conditioned fear memory as a member of the syntaxin super-family (Fujiwara et al 2006). Previous studies have also suggested that SNAP-25 is involved in cognitive dysfunction, verbal memory and memory consolidation (Spellmann et al 2008;Golimbet et al 2010;Hou et al 2004). Moreover, STX1 interacts with SNAP-25 protein, which plays an essential role in the regulation of neurotransmitter release (Lin and Scheller 2000).…”
Section: Discussionmentioning
confidence: 90%